Surgical treatment of movement disorders in neurometabolic conditions - Alonso Zea Vera; Alonso Zea Vera; Andrea L. Gropman; Andrea L. Gropman (Frontiers in Neurology, 2023)
Refractory movement disorders are a common feature of inborn errors of metabolism (IEMs), significantly impacting quality of life and potentially leading to life-threatening complications such as status dystonicus. Surgical techniques, including deep brain stimulation (DBS) and lesioning techniques, represent an additional treatment option. However, the application and benefits of these procedures in neurometabolic conditions is not well understood. This results in challenges selecting surgical candidates and counseling patients preoperatively. In this review, we explore the literature of surgical techniques for the treatment of movement disorders in IEMs. Globus pallidus internus DBS has emerged as a beneficial treatment option for dystonia in Panthotate-Kinase-associated Neurodegeneration. Additionally, several patients with Lesch–Nyhan Disease have shown improvement following pallidal stimulation, with more robust effects on self-injurious behavior than dystonia. Although there are numerous reports describing benefits of DBS for movement disorders in other IEMs, the sample sizes have generally been small, limiting meaningful conclusions. Currently, DBS is preferred to lesioning techniques. However, successful use of pallidotomy and thalamotomy in neurometabolic conditions has been reported and may have a role in selected patients. Surgical techniques have also been used successfully in patients with IEMs to treat status dystonicus. Advancing our knowledge of these treatment options could significantly improve the care for patients with neurometabolic conditions.